Pemberdayaan Masyarakat Dalam Pengkomposan Limbah Padat Pertanian Untuk Keberlanjutan Program Budidaya Atsiri Nilam Di Desa Kesamben Kabupaten Blitar (TEKAD : Teknik Mengabdi, 2024)
Blitar Regency has launched the program "Produk Unggulan Industri Kecamatan" (PUTRI KENCANA), which was expected to increase community empowerment by adopting the philosophy “one village, one product". One of the superior products developed is patchouli, where Kesamben Village is the central area for its development with a land area of 25 ha. The productivity of the cultivated land in producing patchouli plants is only 20% per harvest. It is caused by seasonal issues, land fertility, and the diseases of patchouli if plants are cultivated in unhealthy soil. The use of pesticides and fertilizers did not show good results. Therefore, efforts are needed to provide healthy cultivated land through the application of compost, which can increase the organic content of the soil and improve soil quality. The distillation of patchouli in Kesamben produces 2 tons of solid waste every day, which can be used as raw material for producing compost. Therefore, the aim of the community services is to increase the ability and skills of patchouli farming groups in Blitar Regency to produce compost. The training consists of three activities, namely training on production aspects, management aspects, and monitoring. The production aspect includes a presentation of the theory and practice of making compost on a pilot scale (20 kg/group) and a production scale (2 tons/group). Management aspects include process management to ensure product quality and quantity, as well as economic analysis of the compost. The results showed that participants were very enthusiastic about participating in the training and were able to produce compost both on a pilot scale and on a production scale. Monitoring results showed that participants have used the compost on medicinal plants and vegetables, where the plants grow lush and healthy. Participants have also marketed compost.